Key map of Canadian Arctic Expedition, discoveries in the Arctic Sea 1913 - 1914 and 1917 - 1918 / positions deduced and mapped by the Geodetic Survey of Canada - Geodetic Survey of Canada (1943)
Originally folded in pocket and removed from: "The Friendly Arctic : the story of five years in polar regions" by Vilhjalmur Stefansson, 1943 Color not given